Como percebo o mundo ao meu redor? Uma estratégia de ensino dos sentidos e da percepção que desenvolve habilidades do letramento científico - Fernandes, Cleodon Ronaldo Rego (2022)
Scientific knowledge has been more and more produced and used by humankind to explain phenomena, solve problems and to technology development. Despite the growing impact of science on society, biology teaching has been characterized mainly by the transmission of information without the understanding of nature of science. Several studies show that a meaningful learning, able to develop critical and active students, is potentialized by their engagement in investigative activities that provide and approximation with typical scientific ideas and tools, making them scientific literate. From this perspective, this work aimed to develop Sequences of Investigative Teaching (SIT) with a growing degree of complexity and intellectual freedom about the subjects of sense and perception, together the promotion of scientific literacy in high school students. The main objective was to organize theses sequences in the format of a handbook, allowing their applications by other teachers. This work was performed in two high school classes (2nd and 3rd years) of a public school in the municipality of Natal - RN trough six remote and one presential meetings. Data were collected about all student production and their interaction in the meetings. A quali-quantitative approach and participative research were adopted to analyze the observed phenomena. An analysis of the quantitative and subjective aspects of the student’s production resulted in thematic categories, which were compared with the Program for International Student Assessment (PISA, 2015 edition) framework of knowledges and competences. The activities reached an investigative attribute since the students engaged in problematization and search for answers. Despite these results, it was found students’ difficulty with the typical methods and procediments of science. This teaching proposal can have promoted the acquisition of these knowledges. The learning about sensory systems, sensation and perception resulted in an improvement in the understanding that the brain has a major role in these physiological processes. The model development trough SIT was found an excellent strategy to improve the organization and expression of students’ ideas. We also found that they were able to mobilize the knowledge acquired in previous classes to solve new problems. According to these findings, it has occurred some (re)signification of essential knowledge to the development of scientific literacy, what agrees with some education specialists’ postulates about the necessity of a long-term training in order to promote a real conceptual and attitudinal change.